PEMBERDAYAAN GURU BERBASIS KUALIFIKASI AKADEMIK DI SMP - Laisah Laisah; Zakaria Zakaria; Safnil Safnil (UNIVERSITAS BENGKULU, 2017)
The purpose of this study was to describe how to the teacher empowering based on akademic qualification in the Public High School Srijaya Makmur District of Musi Rawas Nibung North. The method used is descriptive qualitative method. The research subjects principal, vice principal areas of the curriculum, teachers, and supervisors. Methods of data collection put on interviews, observation, and documentation. Analysis of data using qualitative techniques.The results showed management based teacher education qualifications in schools is carried out on the basis of a very strong desire of the management of the school under the command of principal of a school principal to implement in earnest the commitments very full once the applicable provisions, which require the school to carry out a teachers in school management system based on the qualifications and competence of each teachers.